Regional settlement system as a factor of distribution of health care institutions (on example of Volyn region of Ukraine) - Niemets, L.; Niemets, K.; Segida, K.; Pogrebskyi, T. (Toronto: “Toronto Press”, 2014)
The article deals with regional settlement system as a factor of distribution of health care institutions (on example of volyn region of Ukraine). The publication focuses on defining an index of population concentration (which shows how the population is distributed in relation to the total population of the territory) and the main parameters of the spatial distribution of the population (the arithmetic, median and modal centers)
Keywords: settlement􀀃 system; health􀀃 care; population􀀃 density; index􀀃 of􀀃 population􀀃 concentration; arithmetic􀀃center; median􀀃center; modal􀀃center